Characterization of the sand particle size from natural habitat and the digestive tract, as a basis in determining the grain size of sand suitable for a substrate of sea cucumber (Holothuria scabra) culture semiclosed system. Issue 1 (March 2021) - Sabilu, K; Supriyono, E; Nirmala, K; Jusadi, D; Widanarni,
Abstract: The decline in production has prompted researchers in various countries to continue to study factors supporting the success of Holothuria scabra culture. This research aims to evaluate the characteristic of nutrients, size of a sand fraction of the sediment from natural habitats, and the digestive tract, as a basis to determine the grain size of sand suitable for substrates of sea cucumbers culture semi-closed system. The result showed that the highest fraction in the digestive tract of sea cucumber with a wet weight of 5-20 g was clay, 50-70 g of sea cucumbers was fine sand, size of 100-120 g was medium and fine sand, size of 200-220 g was the clay fraction, and in natural habitat was fine sand and clay. Medium sand to clay as a dominant fraction to be found was 86.83±1.22-96.74±0.60%. Smaller sea cucumbers tended to absorb a high amount of coarse sand, while larger sea cucumbers tended to absorb a higher amount of fine sand fraction. Meanwhile, protein, fat, and crude fibre content in the natural habitat sediment was low, so that nutrient enrichment and/or artificial feeding on the substrate is important, to provide for the growth of sea cucumbers if its culture efforts use a semiclosed system.